Paracervical clamps for treatment of uncontrolled postpartum haemorrhage: a novel technique - C. A., Ramalingappa; U., Durga Sireesha; B., Shruthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: PPH is one of the most dreaded third stage complication and is one of the leading cause of maternal mortality and morbidity. Most of the deaths are due to limited availability of pharmacological agents and absent skills to manage PPH. The basis of the study is to introduce a novel technique of application of paracervical clamps transvaginally for temporary occlusion of uterine arteries which represent 90% of blood flow to the uterus. Methods: A prospective study of patients with PPH who did not respond to medical management and who were hemodynamically stable. Paracervical clamps were applied and hemodynamic parameters are continuously monitored. Close monitoring for bleeding PV is done. Clamps are left intact for 6-8 hours and removed. Results: Out of 680 cases of Post-partum haemorrhage. Paracervical clamps were applied to 320 patients from duration of 2013 to 2015 in Karnataka Institute of Medical Sciences and Sushruta Multispeciality Hospital Hubballi. Haemorrhage was effectively controlled in 304 (95.1%) patients and only 16 patients required further surgical management. This non-invasive simple procedure has reduced the rates of surgical management of PPH and the associated morbidity. Conclusions: Application of paracervical clamps is an effective, simple and minimally invasive surgical technique for avoiding excess blood loss in mild to moderate postpartum haemorrhage.